Test-Retest Reliability and Convergent Validity of Piezoelectric Force Plate Measures of Single-Leg Sit-to-Stand Performance in Trained Adults - Makaracı, Yücel; Nas, Kazım; Ruiz-Cárdenas, Juan D; Gündüz, Kerem; Aydemir, Mustafa; Orange, Samuel T (Journal of strength and conditioning research, 2023)
Makaracı, Y, Nas, K, Ruiz-Cárdenas, JD, Gündüz, K, Aydemir, M, and Orange, ST. Test-retest reliability and convergent validity of piezoelectric force plate measures of single-leg sit-to-stand performance in trained adults. J Strength Cond Res 37(12): 2373-2380, 2023-The single-leg sit-to-stand (STS) test has emerged as a promising method of assessing lower-limb functional strength and asymmetry. However, the reliability of its performance parameters on a force plate has not been explored. This study examined the test-retest reliability and convergent validity of the single-leg STS test performed on a piezoelectric-based force plate in trained subjects. Thirty trained male adults (age: 21.4 ± 1.7 years) performed 3 separate single-leg STS days of testing to assess both intraday and interday reliability. Performance parameters included STS time, ground reaction force (GRF), and center of pressure (CoP) sway velocity. The relationship between single-leg STS parameters and unilateral countermovement jump (CMJ) variables was assessed for convergent validity. Intraclass correlation coefficient (ICC) and coefficient of variation (CV) were calculated for reliability analyses, and convergent validity was assessed with Spearman's correlation coefficient (ρ). In the dominant leg, single-leg performance parameters showed moderate-to-excellent intraday reliability (ICC = 0.65-0.90, CV = 4.3-11.2%) and moderate interday reliability (ICC = 0.54-0.74, CV = 5.8-13.5%). In the nondominant leg, all single-leg STS performance parameters showed good intraday (ICC = 0.79-0.86, CV = 3.8-9.8%) and interday reliability (ICC = 0.75-0.82, CV = 4.6-9.7%). STS times in the dominant and nondominant legs were inversely related to unilateral CMJ velocity (ρ = -0.47 and -0.38, respectively). CoP sway velocity in the nondominant leg showed positive correlations with unilateral CMJ power and velocity (ρ = 0.38 and 0.54, respectively). In conclusion, the force plate-based single-leg STS test provides reliable measures of STS time, GRF, and CoP sway velocity in trained adults and could be used to assess lower-limb function and asymmetry.